1999
DOI: 10.1097/00001888-199904000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Why students drop out of the pipeline to health professions careers

Abstract: Early intervention is important to retaining students in a pipeline that leads to a health care career. Summer programs are successful, but may not be enough to help students with difficult science courses in college, especially chemistry. However, another important conclusion is that much more needs to be done to help students find mentors with whom they can develop relationships and to give them opportunities to work in health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Previous studies support the importance of early exposure to the health professions (Suarez and Shanklin 2002;Thurmond 1999;Wiggs 2000) and indicate that early knowledge of genetic counseling appears to increase the likelihood a student will consider the profession as a career (Oh and Lewis 2005). Since greater than 60% of all respondents and greater than 77% of African American respondents reported that they had already decided on a career, recruitment efforts targeting African Americans should focus on students before they enter college.…”
Section: Internetmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies support the importance of early exposure to the health professions (Suarez and Shanklin 2002;Thurmond 1999;Wiggs 2000) and indicate that early knowledge of genetic counseling appears to increase the likelihood a student will consider the profession as a career (Oh and Lewis 2005). Since greater than 60% of all respondents and greater than 77% of African American respondents reported that they had already decided on a career, recruitment efforts targeting African Americans should focus on students before they enter college.…”
Section: Internetmentioning
confidence: 97%
“…The literature cites other factors that differ between African American and Caucasian students when they consider other health careers including finances, standardized tests and application criteria, impact of role models and mentors, outreach efforts, awareness of opportunities, early exposure to the health professions, and social networks (Brazziel 1997;Dowell 1996;Lease 2004;Wiggs 2000;Zhou et al 2004). Many studies have investigated African American recruitment into other health professions (Baldwin 2003;Butters 2002;Dowell 1996;Suarez and Shanklin 2002;Thurmond 1999;Wiggs 2000), science (Brazziel 1997), and other related fields (Morssink et al 1996;Zhou et al 2004), but there is limited literature focusing on the unique recruitment barriers in genetic counseling (Mittman and Downs 2008;Oh and Lewis 2005;Schoonveld et al 2005;Smith et al 1993;Warren 2004aWarren , b, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have also identified chemistry courses as a principal factor discouraging premedical interest among gifted URM students who had participated in a high school science enrichment program (Thurmond and Cregler 1999) and among students at a liberal arts college (Lovecchio and Dundes 2002). A number of authors have questioned the continuing role chemistry courses play in thinning the undergraduate cohort of premedical students (Emanuel 2006; Dienstag 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thurmond and Cregler (1999) have suggested that early intervention directed at basic science courses is important to maintaining students' interest in, and progression through, the medical pipeline. Moreover, URM students can have negative experiences with science education due to issues with scientific identity (Carlone, Haun-Frank, & Webb, 2011;Hazari, Sadler, & Sonnert, 2013) and with their relationships with primary and secondary science teachers (Kitts, 2009;Mcharg, Mattick, & Knight, 2007).…”
Section: Academic Factors Predicting Interest In Medicinementioning
confidence: 99%